Optimizing the Electronic Structure of Ruthenium Oxide by Neodymium Doping for Enhanced Acidic Oxygen Evolution Catalysis. (5th January 2023) - Li, Lu; Zhang, Gengwei; Xu, Jingwen; He, Huijie; Wang, Bin; Yang, Zhimao; Yang, Shengchun
Abstract: It is a great challenge to design active and durable oxygen evolution reaction (OER) electrocatalysts for proton exchange membrane (PEM) electrolyzer due to the high dissolution of electrocatalysts in acidic solution. Herein, the Nd‐doped RuO2 (Nd0.1 RuOx ) is developed for enhanced oxygen evolution in 0.5 m H2 SO4 solution with an overpotential of 211 mV to achieve 10 mA cm −2 . The theoretical calculation reveals that the improved activity of Nd0.1 RuOx is due to the moderate decrease of d‐band center energy, which balances the adsorption and desorption of oxygen intermediates. Moreover, the formation of more high valence state Ru 4+ in Nd0.1 RuOx is beneficial to the chemical stability of Ru species during the OER process, indicating that the introduction of Nd can effectively suppress the dissolution of Ru in acidic electrolytes. In addition, the PEM electrolyzer using Nd0.1 RuOx /CC as the anode can be operated at 10 mA cm −2 stably for 50 h. This study sheds new light on the design of the OER catalysts in acid by engineering the electronic structure of RuO2 . Abstract : The introduction of Nd can effectively modulate the d‐band center and increase the ratio of high state Ru 4+ . Benefiting from the optimization of the electronic structure by Nd doping, the Nd0.1 RuOx catalyst displays outstanding catalytic activity with an overpotential of merely 211 mV @ 10 mA cm −2, as well as good stability.